2019
DOI: 10.21203/rs.2.18114/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between the efficacy of stem cell therapy for osteonecrosis of the femoral head and cell viability

Abstract: Background: Osteonecrosis of the femoral head (ONFH) is a common disease that greatly affects the quality of life of patients. Repair of the necrotic area is key to successful treatment. Currently, the combination of stem cell transplantation and decompression is used clinically to promote the repair of necrotic areas based on the characteristics of stem cells. However, a considerable number of patients do not achieve a satisfactory outcome in terms of repair of the femoral head necrotic area, and it is very i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The researchers found a high level of interleukin-6 and tumor necrosis factor-α at an advanced stage of FHN. Thus it was found that cytokine activity accelerated when used in combination with growth factor, which can be further used in future studies [70][71][72][73][74][75][76] .…”
Section: Femoral Head Osteonecrosis Treatment Through Growth Factorsmentioning
confidence: 99%
“…The researchers found a high level of interleukin-6 and tumor necrosis factor-α at an advanced stage of FHN. Thus it was found that cytokine activity accelerated when used in combination with growth factor, which can be further used in future studies [70][71][72][73][74][75][76] .…”
Section: Femoral Head Osteonecrosis Treatment Through Growth Factorsmentioning
confidence: 99%